Regional Employment Impacts of Biorefineries in the EU - Benz Xinqi Zhu; Maria Vrachioli; Johannes Sauer (EuroChoices, 2023)
The European Commission aims to achieve a climate-neutral economy by 2050 and positively affect the employment growth rate while reducing fossil-based production activities. For that reason, according to the European Green Deal, decarbonisation and modernisation of fossil-based industries is essential. Thus, replacing fossil fuel-based inputs in these industries with bio-based inputs through the establishment of biorefineries can contribute towards this goal. This article reports the results of a study on the impact of biorefineries on the regional employment rate, and other regional socio-economic indicators. A unique regional level dataset provided by EU Joint Research Centre and the EU H2020 BioMonitor project is used to examine the impact of the biorefinery industry on local employment. This dataset covers multiple European Member States and enables us to account for regional characteristics over a 10-year period (2009–2018). Our results show that introducing biorefineries to a region can be associated with a higher regional employment growth compared to regions with no biorefineries. Improving biorefinery data availability and quality can assist further the research in this area and promote the development of bioeconomy in Europe.
Keywords: 630